A new system for classifying accessory canal morphology. (31st July 2017) - Ahmed, H. M. A.; Neelakantan, P.; Dummer, P. M. H.
Abstract: Thorough knowledge of anatomical complexities of the root canal system has a direct impact on the effectiveness of canal preparation and filling, and is an essential prerequisite for successful root canal treatment. A wide range of complex variations in root canal anatomy exists, including root canal configuration type, developmental anomalies and minor canal morphology such as accessory canals and apical deltas. Accessory canals and apical deltas have been associated with pulp disease, primary canal infection, canal reinfection and post‐treatment disease. The current definitions of accessory canal anatomy are not standardized and potentially confusing. Given their role in endodontic disease and their impact on treatment outcomes, there is a need to have a simple classification of their anatomy to provide an accurate description of their position and path from the canal to the external surface of the root. The purpose of this article is to introduce a new system for classifying accessory canal morphology for use in research, clinical practice and training.